2021
DOI: 10.1155/2021/6640206
|View full text |Cite
|
Sign up to set email alerts
|

Potential Novel Therapies for Neurodevelopmental Diseases Targeting Oxidative Stress

Abstract: Neurodevelopmental disorders are a category of diseases that is not yet fully understood. Due to their common traits and pathways, often it is difficult to differentiate between them based on their symptoms only. A series of hypotheses are trying to define their etiology, such as neuroinflammation, neurodegeneration, and immunology, but none have managed to explain their multifactorial manifestation. One feature that may link all theories is that of oxidative stress, with a redox imbalance as well as several o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 106 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…NAC is the acetylated form of cysteine, which could be used for synthesizing the potent endogenous antioxidant glutathione. Mounting evidence shows augmented oxidative stress in neuropsychiatric diseases and corresponding animal models [ 67 , 68 , 69 ], and dietary supplements of an antioxidant such as NAC have shown substantial benefits [ 38 , 39 , 70 ]. Our results were in line with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…NAC is the acetylated form of cysteine, which could be used for synthesizing the potent endogenous antioxidant glutathione. Mounting evidence shows augmented oxidative stress in neuropsychiatric diseases and corresponding animal models [ 67 , 68 , 69 ], and dietary supplements of an antioxidant such as NAC have shown substantial benefits [ 38 , 39 , 70 ]. Our results were in line with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…To further boost the therapeutic efficiency of antioxidants, research is being done on how well nanoparticles and nanocarriers can carry antioxidants to specific cellular compartments or tissues, enhance their bioavailability, and stabilize them. Promising advances in gene therapy and editing technologies have the ability to directly modify genes implicated in antioxidant defense systems, which could raise endogenous antioxidant enzyme levels or change pathways connected to OS [96,97]. Furthermore, studies explore bioactive substances derived from plants and other natural sources that possess strong antioxidant capabilities, offering possible treatments for disorders associated with OS.…”
Section: Novel Therapies Targeting Osmentioning
confidence: 99%
“…In fact, the ASD postmortem brain samples analysis indicated the presence of brain mitochondrial dysfunction proved by the existence of discrepancies in gene expression, a decrease in the electron transport chain activity as well as a decrease in the tricarboxylic acid cycle enzyme [ 41 ]. Furthermore, the contribution of oxidative stress was also observed as one of the causes of this disorder [ 42 ]. So, it not surprising that several studies found a connection between dietary deficiencies and ASD, as a consequence.…”
Section: Bioactive Compounds From Plants As Antioxidant Anti-inflamma...mentioning
confidence: 99%
“…So, it not surprising that several studies found a connection between dietary deficiencies and ASD, as a consequence. To help ASD individuals, several plant-based bioactive compounds have been studied as a complement to ASD therapy [ 42 , 43 ].…”
Section: Bioactive Compounds From Plants As Antioxidant Anti-inflamma...mentioning
confidence: 99%
See 1 more Smart Citation